1998
DOI: 10.1093/nar/26.23.5388
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human Rad51 recombination protein with single-stranded DNA binding protein, RPA

Abstract: Replication protein A (RPA), a heterotrimeric single-stranded DNA binding protein, is required for recombination, and stimulates homologous pairing and DNA strand exchange promoted in vitro by human recombination protein HsRad51. Co-immunoprecipitation revealed that purified RPA interacts physically with HsRad51, as well as with HsDmc1, the homolog that is expressed specifically in meiosis. The interaction with HsRad51 was mediated by the 70 kDa subunit of RPA, and according to experiments with deletion mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
138
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 55 publications
10
138
0
Order By: Relevance
“…The observation that yeast sgs1 or srs2 mutants die for the accumulation of hyperrecombination events could be extended in human cells according to our findings. Moreover, because it has been recently reported that WRN relocalizes to sites of replication arrest after HU treatment, colocalizing with RPA (Costantinou et al, 2000), and on the basis of the documented interaction of RAD51 with RPA (Golub et al, 1998), our observation could also reinforce the hypothesized interaction of WRN and RAD51 in resolving replication conflicts. …”
supporting
confidence: 80%
“…The observation that yeast sgs1 or srs2 mutants die for the accumulation of hyperrecombination events could be extended in human cells according to our findings. Moreover, because it has been recently reported that WRN relocalizes to sites of replication arrest after HU treatment, colocalizing with RPA (Costantinou et al, 2000), and on the basis of the documented interaction of RAD51 with RPA (Golub et al, 1998), our observation could also reinforce the hypothesized interaction of WRN and RAD51 in resolving replication conflicts. …”
supporting
confidence: 80%
“…RAD51 foci are seen at high levels in cells exposed to DNAdamaging treatments such as ionizing radiation (Haaf et al, 1995;Scully et al, 1997a). Similar foci have also been observed in mitotic S-phase cells and are thought to identify sites where stalled or broken replication forks undergo repair (Tashiro et al, 1996;Golub et al, 1998;Raderschall et al, 1999). Consistent with a role in the repair of DSBs, RAD51 foci form during meiosis at the time when genetically programmed DSBs are generated (Plug et al, 1996;Barlow et al, 1997;Moens et al, 1997;Scully et al, 1997b).…”
Section: Introductionmentioning
confidence: 81%
“…Immunostaining techniques can detect assembly of recombination proteins into subnuclear staining foci (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Several lines of evidence suggest that these foci represent protein oligomers assembled at sites of DSBs and possibly daughter strand gaps as well.…”
Section: Reca-like Recombinases Assemble On Single-strand Dna (Ssdna)mentioning
confidence: 99%
“…Double staining shows that multiple proteins required for recombination assemble at the same sites during recombination. Such experiments in yeast and mammalian cells showed that RPA colocalizes with Rad51 (29,(31)(32)(33). An important question raised by the biochemical interaction of ssb and recombinase is: Does ssb assemble before or after recombinase in vivo?…”
Section: Reca-like Recombinases Assemble On Single-strand Dna (Ssdna)mentioning
confidence: 99%